STABILITAS WAKTU PENYIMPANAN SERUM, PLASMA K3EDTA, DAN PLASMA HEPARIN PADA SUHU RUANG TERHADAP PEMERIKSAAN KADAR TRIGLISERIDA - Naqiyyah, Salsabilla (Jurnal Kesehatan Siliwangi, 2024)
Triglyceride examination in the laboratory sometimes experiences delays caused by several factors, such as damage to the equipment, running out of reagents, and obstacles when sending reference samples. Stability is the ability of a sample to maintain the initial value of the measured analyte within a certain period under specified storage conditions. One of the factors that can affect stability is storage temperature. The purpose of this study was to determine the stability of triglyceride levels in serum, K3EDTA plasma, and heparin plasma which were examined immediately and stored at room temperature for 1, 2, and 3 days. This type of research is experimental research with a quasi-experimental research design, which provides storage treatment for serum specimens, K3EDTA plasma, and heparin plasma after centrifugation. The statistical test used was the General Linear Model (GLM) test. The results showed that serum and heparin plasma specimens had significant differences (Sig.0.000) in 2-day storage. While the K3EDTA plasma sample had significant differences (Sig.0.009) in 3-day storage. So it can be concluded that there is a difference in the stability of triglyceride levels in serum, K3EDTA plasma, and heparin plasma after storage at room temperature. Triglyceride levels in serum and heparin plasma specimens are stable for 1 day at room temperature. While triglyceride levels in K3EDTA plasma are stable for 2 days at room temperature. However, there is no clinical difference in serum, K3EDTA plasma, and heparin plasma specimens.